PA.01 The dorsal hippocampal commissure: when the functionality matters. Issue 8 (7th July 2011) - Rosenzweig, I; Beniczky, S; Brunnhuber, F; Alarcon, G; Valentin, A
Abstract : Aims: The human hippocampal phylogeny is manifested by near or total disappearance of ventral hippocampal commissure. In contrast, the dorsal hippocampal commissure, although considered controversial and vehemently disputed by some groups, is believed to present a functional pathway in the human brain. Methods: Gloor et al in 1993 proposed that, in humans, the spread though the dorsal hippocampal commissure is the only likely pathway of contralateral propagation for seizure discharges originating in mesial temporal structures with spread to the contralateral hippocampus. Results: We report an unusual case of a patient with refractory temporal epilepsy (TLE) with several seizure types who underwent a comprehensive presurgical evaluation due to non-concordant results between various investigative modalities. Conclusions: It is postulated here that repeated false lateralisation of seizure onset by extracranial EEG recordings in our patient might have been instigated by the distinct patterns of seizure spread utilising the dorsal hippocampal commissure.